RELEVANT FACTORS FOR BUILDING COMPETITIVENESS OF MANUFACTURING INDUSTRY IN BOSNIA AND HERZEGOVINA - Merim Kasumović; Vildana Altumbabić (Economic Review)
Competitiveness of an industry is conditioned by a number of different factors. These factors may be a part of macroeconomic or microeconomic competitiveness. In essence, macroeconomic competitiveness creates preconditions for generation of microeconomic competitiveness. It is therefore important to identify relevant factors for generation of industry competitiveness in order to promote the microeconomic competitiveness of an industry through adequate macroeconomic competitiveness and industrial policy. In often cases, the government creates industrial policies to encourage development of a particular industry, but these policies do not have targeted effects. By identifying relevant factors of industrial competitiveness, industrial policy will be focused on them, thus avoiding waste of scarce resources and facilitating achievement of industrial policy objectives. This paper examines relevant factors of competitiveness of Bosnia and Herzegovina’s (BiH) manufacturing industry in the period 2010-2017 as basis for its successful long-term growth and development. These factors should be a focal point of industrial policy makers in BiH manufacturing industry.